Web based support for pregnant mother - Salameh, Anas A.Mohammad; Alkafagi, Alaa Ahmed Chyad; Khunsri, Chulawadee; Habbal, Adib M. Monzer (2011)
This paper reports on a work on progress. A web-based system has been developed to ensure pregnant mothers be notified regarding their pregnancy progress.The design and development of the system which is named Pregnancy Progress System (PregProSyst) are outlined.In addition, an initial test with potential users including pregnant mothers and healthcare practitioners is also discussed. It is found that potential users agree that PregProSyst is good for them and they are happy to use the system.